(untitled) (INNOVATIVE ECONOMY, 2022)
Karpenko V.L. ANALYSIS OF THE DOMESTIC DAIRY MARKET: REALITIES AND PROSPECTS Purpose. The aim of the article is the analysis of the dynamics of development of the domestic dairy market. Methodology of research. The following methods are used in the research process: monographic, comparative analysis – in assessing the general trends in the dynamics of indicators of the level of milk production, its processing, evaluation of milk processing enterprises; graphic – when displaying the production of basic dairy products; abstract and logical – in preparing conclusions. Findings. The dynamics of milk production in Ukraine, the dynamics of milk production per capita in all categories of farms and the dynamics of dairy production in Ukraine are analysed. The key players – processors in the dairy market have been identified. The dynamics of average prices of milk sales by agricultural enterprises of all forms of ownership is estimated. The structure of dairy production in 2020 and the structure of the largest dairy producers in 2020 are substantiated. It has been suggested that in order to increase the efficiency of milk processing enterprises, it is advisable to build partnerships between all market participants, which will create the necessary economic conditions for increasing the number of dairy cows through the equivalent pricing mechanism and, consequently, increase milk production. Originality. Ways to improve the functioning of milk processing enterprises by improving the creativity of the marketing system, the range of dairy products, the introduction of new dairy products to consumers (eco-products), improving the quality of milk as a raw material. Practical value. The results of the study can be used in the formation of development strategies, as well as in determining the reserves of economic growth of dairy enterprises in Ukraine. Prospects of functioning of dairy producers of the country are substantiated. Key words: market of milk and dairy products; production of dairy products; cream; butter; cheese; yogurt; milk processing enterprise.